Human evolution - Brown, George D., 1931- (Dubuque, IA : Wm. C. Brown Publishers, 1995)
This work is intended for use with supporting material in an introductory level, multidisciplinary college course. Its audience are students who are not majoring in one of the sciences directly pertaining to human origins, e.g. biology, geology, and anthropology.... This text provide[s] a better understanding of the fundamental aspects of human evolution by placing them in an integrated context with all of nature. -Pref.
Why? -- Darwin's idea -- Primates -- Humans and apes compared -- Primate pathway -- Rise of hominids -- Australopithecines -- Humans appear, Homo habilis -- Great migration, Homo erectus -- Neandertals arrive -- Cro-magnons -- Rise of modern humans.
Includes bibliographical references (p. 243-253) and index.
Nafisa
Keywords: Human evolution